Employee Well-being Programs: Assessing the Impact on Engagement, Productivity, and Retention - Joko Bagio Santoso (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Employee wellness programs have become an important focus in efforts to increase employee engagement, productivity and retention in organizations. This research aims to explore the relationship between employee welfare programs and key variables such as employee engagement, productivity and retention. Using a systematic literature review approach, this research analyzes findings from various relevant studies and surveys. The results show that factors such as employee empowerment, managerial support, growth opportunities, a supportive work environment, and company policies that support work-life balance have a significant relationship with employee engagement, productivity, and retention. Practical implications of these findings are discussed, along with study limitations and suggestions for future research.